Development of an Android-Based Physical Fitness Measurement Test with Kodular Application for Junior High School Students in Singkawang City - Mustakim Mustakim; Zusyah Porja Daryanto; Ade Rahmat (UNIVERSITAS NEGERI MAKASSAR, 2024)
Technological advancement, especially in Android smartphones, is on the rise in Indonesia. An innovative solution is the creation and evaluation of physical fitness tests for junior high school students in Singkawang through an Android-based application using Kodular. The application is easily accessible to coaches, teachers, students, and parents and provides instructions on physical fitness test implementation procedures and test norms. This study was a research and development methodology involving a media expert and a materials expert. The test was conducted in two phases. The first phase involved 15 students of SMPN15 Singkawang, and the second phase involved 21 futsal players and 21 students of SMPN 15 Singkawang. The results of the small-scale test showed that 87% of the respondents rated the application as very feasible, while 13% rated it as feasible. The results of the large-scale test showed that 80% of the respondents rated the application as very feasible, and 20% rated it as feasible. Therefore, the Android-based physical fitness testing application with Kodular is declared feasible for general testing. This application helps trainers or teachers know the norms and values of physical fitness tests digitally and efficiently.